2017
DOI: 10.1016/j.chaos.2017.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Spatial analysis of cities using Renyi entropy and fractal parameters

Abstract: The spatial distributions of cities fall into two groups: one is the simple distribution with characteristic scale (e.g. exponential distribution), and the other is the complex distribution without characteristic scale (e.g. power-law distribution). The latter belongs to scale-free distributions, which can be modeled with fractal geometry. However, fractal dimension is not suitable for the former distribution. In contrast, spatial entropy can be used to measure any types of urban distributions. This paper is d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 39 publications
(54 reference statements)
0
11
0
Order By: Relevance
“…In previous studies, fractal analysis of tree cover and deforested areas were calculated by using the FFI [40,57,58], Fixed Grid 2D Lacunarity (FG2DL) [59]. Until now, fractal analysis was used in urban agglomeration, urban growth [60][61][62], or green infrastructure models of cities [63].…”
Section: Use Of Glcm and Fractal Analysis For Quantification The Defomentioning
confidence: 99%
“…In previous studies, fractal analysis of tree cover and deforested areas were calculated by using the FFI [40,57,58], Fixed Grid 2D Lacunarity (FG2DL) [59]. Until now, fractal analysis was used in urban agglomeration, urban growth [60][61][62], or green infrastructure models of cities [63].…”
Section: Use Of Glcm and Fractal Analysis For Quantification The Defomentioning
confidence: 99%
“…Fractal dimension can be used to act as the characteristic parameter of urban description. This problem has been preliminarily researched in previous works [ 8 , 25 ]. In one companion paper, using the box-counting method, we revealed that spatial entropies depend on the scales of measurement, and the normalized entropy values are empirically equal to the normalized fractal dimension values [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Three typical fractal dimensions in global multifractal dimensions, i.e., capacity dimension D 0 , information dimension D 1 , and correlation dimension D 2 , are discussed in this research, but the results have not been generalized to multifractal parameter spectrums. In another companion paper, based on area radius scaling, the normalized Renyi entropy is generalized to multifractal spectrums [ 25 ]. Two sets of multifractal indicators are proposed to describe urban growth and form.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations